ANALYSIS OF FACTORS THAT AFFECTING THE EXPORT OF WOODEN CRAFT - Adiyadnya, Made Santana Putra; Ardianti, Putu Novia Hapsari (Jurnal Riset Akuntansi (JUARA), 2019)
Indonesia as a developing country always to increase development, with the main goal is to be realize a democratic society and to be prosperous country. International trade can create profits with provide opportunities to each country in export sector from manufactured goods or services. The government is expected to be able to develop competitiveness of Balinese handÂicraft products in export sector of woods craft optimally, then this condition will contribute for Indonesiaâ€™s foreign exchange reserves. Art in Bali is one thing attraction for tourists, so many wooden craft traders who showcased his work for sale to tourists. The purpose of this study are: 1) to know the effect of tourist visits, inflation and exchange rate of US Dollar and simultaneous to export of wooden crafts in the Province of Bali; 2) to know the effect of tourist visits, inflation and exchange rate of US Dollar and partial to export of woodÂen crafts in the Province of Bali. The result of this research were: 1) effect of tourist visits, inflation and exchange rate of US Dollar and simultaneous to export of wooden crafts in the Province of Bali was significant; 2) variable tourist visits and the US Dollar exchange rate has a positive and significant effect to export of wooden crafts in the Province of Bali, then inflation have no partial effect to export of wooden crafts in the Province of Bali.